How Much BMI and Physical Activity Level Induce Elevated Uric Acid? - Muhlisoh Muhlisoh; Asni Hanif Hasaini; Martini Nur Sukmawaty (Indonesian Journal of Global Health Research, 2023)
Gout is a disease by elevated uric acid that is categorized as a degenerative disease by process of decreasing organ function which generally occurs in old age but can also occur in adulthood due to decreased health status. The epidemiological studies showed that a high BMI triggers risk factors for lifestyle-related diseases such as type 2 diabetes, cardiovascular disease, cancer, and high uric acid. The other finding stated that regular exercise produces an immunomodulatory effect, which may contribute to health benefits. Despite the high prevalence of gout and evidence that underscores the benefits of physical activity in rheumatic diseases, there has been no discussion about the link between Body Mass Index (BMI), physical activity and elevated uric acid. The main objective is to analyze the body mass index and level of activity on uric acid levels, and the first specific objective is to describe the characteristics of the responden. The study conducted in Martapura 1 Public Health Center by an observational cross sectional design using linear regression models. Thirty respondents were collected using simple random sampling and questionnaire containing the result of BMI, physical activity level and uric acid was used to measure the data. There is a significant effect between BMI and physical activity together on uric acid levels. The BMI value obtained f count > f table (3.800 > 2.0484) means that partially BMI has a positive effect on uric acid. Physical activity value obtained f count > f table (-1.610 <2.0484) means H0 is accepted Conclusions: Research showed that an increase in BMI can increase uric acid levels by controlling variabel of physical activity (B=0,27, P=0.001 in BMI; B=-0.002, P=0.119 in physical activity).